Investigations into methods to improve the antibacterial activity of Acticoat. Issue 5 (1st May 2016) - Ravensdale, Joshua; Wood, Fiona; O'Brien, Francis; Gregg, Keith
Abstract : N/A: Multiple studies have shown that the antibacterial dressing Acticoat can inhibit growth of bacteria but is unable to completely clear a wound of infection, which could leave patients vulnerable to sepsis. Agar inoculated with four different Staphylococcus aureus strains and overlain with Acticoat showed growth inhibition beneath and within a 1 mm perimeter of the dressing after 24 h. When lifted from inoculated agar and briefly blotted onto fresh agar plates, Acticoat transferred viable bacteria. Scanning electron microscopy of the surface of Acticoat that overlaid meticillin‐resistant S. aureus for 24, 48 and 72 h showed dense clusters of apparently undamaged bacteria distributed across the mesh. The number of bacteria growing on inoculated pig skin, underneath and on the surface of Acticoat, was lower than on controls for the first 8 h, but after 24 h the number of bacteria on the skin was 2.3‐fold greater than the untreated controls. In contrast, after 24 h the number of bacteria surviving on the surface of the Acticoat was 11.9 % of controls. Acticoat moistened with 10 % glycerol plus antimicrobial peptides (AMPs) mel12–26 or bac8c (50 μg ml − 1 ) reduced the numbers of bacteria on the dressing and on the skin underneath to below 10 % and 0.01 % of the controls, respectively. When lysozyme (1 mg ml − 1 ) was added to Acticoat wetted with glycerol and the AMP bac8c, the dressing was able to prevent the survival of bacteria on densely inoculated pig skin and on the surface of Acticoat for up to 24 h. In effect, biocompatible solvents and AMPs significantly enhance the bactericidal efficacy of Acticoat.